What can digital humanities do for literary adaptation studies: distant reading of children's editions of Robinson Crusoe. - Hui, Haifeng (Digital Scholarship in the Humanities, 2023)
While digital humanities has emerged as a cutting-edge research trend in the humanities over the past two decades, its application in literary research is still scarce. At present, the field of digital humanities for literary studies is largely focused on theoretical development, critical reflections, and infrastructure building. This article aims to explore the potential of digital humanities in advancing literary research through critical practices and elucidates the distinctive advantages of employing digital humanities methodologies in the study of literature. In this article, a dozen of children's editions of Robinson Crusoe from different historical periods are used as the corpus, and methods such as word cloud, keyword extraction, and sentiment analysis using Python are used to examine the adaptation of Defoe's original novel in children's editions and to uncover a positive inclination throughout the diachronic evolution of children's literature adaptations. It has also revealed some patterns within the intricate details of the different children's editions. In doing so, the article demonstrates the unique advantages of digital humanities in literary studies and proposes new ways of applying digital humanities to literary criticism.